Does IT Help? : Information Technology in Banking and Entrepreneurship - Ahnert, Toni (IMF Working Papers; Working Paper, 2021)
This paper analyzes the importance of information technology (IT) in banking for entrepreneurship. To guide our empirical analysis, we build a parsimonious model of bank screening and lending that predicts that IT in banking can spur entrepreneurship by making it easier for startups to borrow against collateral. We provide empirical evidence that job creation by young firms is stronger in US counties that are more exposed to ITintensive banks. Consistent with a strengthened collateral lending channel for IT banks, entrepreneurship increases more in IT-exposed counties when house prices rise. In line with the model's implications, IT in banking increases startup activity without diminishing startup quality and it also weakens the importance of geographical distance between borrowers and lenders. These results suggest that banks' IT adoption can increase dynamism and productivity.